2004
DOI: 10.1080/08958370490439687
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Toxicity of Manganese Sulfate and Manganese Phosphate in Young Male Rats Following Subchronic (13-Week) Inhalation Exposure

Abstract: Growing evidence suggests that nasal deposition and transport along the olfactory nerve represents a route by which inhaled manganese and certain other metals are delivered to the rodent brain. The toxicological significance of olfactory transport of manganese remains poorly defined. In rats, repeated intranasal instillation of manganese chloride results in injury to the olfactory epithelium and neurotoxicity as evidenced by increased glial fibrillary acidic protein (GFAP) concentrations in olfactory bulb astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…Higher relative concentrations of test compounds are generally needed to elicit responses in cell cultures due to the acute nature of the treatment period in in vitro studies (hours to days) compared with chronic long-term studies in animal models (days to months). Importantly, the 300 M manganese concentration used in this study approximates the concentration observed in the striatum of manganese treated rats (Chan et al, 1992;Erikson and Aschner, 2003;Dorman et al, 2004;Gunter et al, 2004). We observed activation of apoptotic signaling molecules, including PKC␦ cleavage, at lower manganese concentrations (50 M) when N27 cells were incubated over a longer time (72 h) (unpublished observations).…”
Section: Discussionmentioning
confidence: 82%
“…Higher relative concentrations of test compounds are generally needed to elicit responses in cell cultures due to the acute nature of the treatment period in in vitro studies (hours to days) compared with chronic long-term studies in animal models (days to months). Importantly, the 300 M manganese concentration used in this study approximates the concentration observed in the striatum of manganese treated rats (Chan et al, 1992;Erikson and Aschner, 2003;Dorman et al, 2004;Gunter et al, 2004). We observed activation of apoptotic signaling molecules, including PKC␦ cleavage, at lower manganese concentrations (50 M) when N27 cells were incubated over a longer time (72 h) (unpublished observations).…”
Section: Discussionmentioning
confidence: 82%
“…However, in the case of inhalation, the relationship between cumulative dose and target size dose may be different from that of other exposure routes, as it appears that a fraction of the manganese inhaled may bypass the circulatory system and be directly taken into the brain through retrograde transport via the olfactory neuronal pathway and the trigeminal system (Brenneman et al 2000;Dorman et al 2002Dorman et al , 2004Henriksson andTjalve 2000, Lewis et al 2005). Thus, manganese uptake via inhalation may produce higher target (brain) doses than equal manganese uptake via other routes.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory nerve is speculated to be the most likely pathway for the transport of intranasally instilled NPs to the brain [30,63,64]. High accumulation, oxidative stress, and obvious morphological alteration of hippocampal neurons and olfactory bulb were detected after nasal exposure to TNPs [65].…”
Section: Brain and Cnsmentioning
confidence: 99%